A Psycholinguistic Analysis of Language Patterns and Rhetorical Strategies of Intellectual Independence in Disney Princess Characters - Nygmanova, A.Y. (MAQSUT NARIKBAYEV UNIVERSITY School of Liberal Arts. Astana, 2025)
The research investigates how Disney princess films throughout three time periods (Classic 1937-1950, Renaissance 1989-1991, Modern 2013-2021) create linguistic structures to express female intellectual independence and agency. The research uses Fairclough’s Critical Discourse Analysis together with psycholinguistic theory and intersectionality to examine speech acts and rhetorical strategies in chosen film scripts. The research shows how Disney princesses have evolved from passive romantic figures into independent protagonists who demonstrate both assertiveness and cognitive independence through characters like Elsa and Moana. The research investigates cultural identity and leadership in non-Western contexts while adding to gender, media, and psycholinguistic studies by showing how language shapes female autonomy and agency
Keywords: Disney princesses, gender representation, discourse analysis, psycholinguistics, intersectionality, female agency